Ivonescimab: The Two Pronged Attack - Vallathol, Dilip Harindran; Menon, Abhinav; Warrier, Arun R. (Indian Journal of Medical and Paediatric Oncology, 2025)
Targeted therapy and immunotherapy have changed the landscape of treatment of cancers with respect to longevity and quality of life. Programmed death 1 (PD-1) and vascular endothelial growth factor (VEGF) are very salient targets of anticancer drugs. Dual blockade with bispecific antibodies is a novel mode of treatment of malignancies, which has already been successful in hematological malignancies. Ivonescimab, a novel bispecific antibody that targets PD-1 and VEGF, has been developed in China. It has been found to be beneficial in nonsmall cell lung cancer, biliary tract cancers, and breast cancers for which phase 3 clinical trials have already been discussed in various meetings and publications. The current drug review is regarding the parameters of this novel drug—the mechanism of action, clinical and preclinical trials, and approvals.
Keywords: ivonescimab; VEGF; PD-1; targeted therapy; immunotherapy